2022
DOI: 10.1002/ijc.34315
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and response to next‐generation sequencing‐guided therapy in locally advanced or metastatic esophageal cancer

Abstract: Esophageal cancer (EC) is a main cause of cancer‐related deaths. However, genomic alterations and the clinical value of next‐generation sequencing (NGS) in advanced or metastatic EC for precision therapy remain largely unclear. Herein, we performed comprehensive analyses on a cohort of 47 individuals with advanced or metastatic EC who underwent NGS between May 2017 and February 2020. Eventually, 227 mutated genes were identified in the cohort. TP53, NQO1, DPYD, GSTM1, XRCC1 and ERCC1 were the most mutated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…TP53 is linked to a poorer outcome in ESCA. Patients with TTN, MUC16 mutations have a higher tumor mutation load and may benefit from immunotherapy ( 33 35 ). As a result, patients with a high level of CDKL3 expression may benefit less from immunotherapy and result in a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 is linked to a poorer outcome in ESCA. Patients with TTN, MUC16 mutations have a higher tumor mutation load and may benefit from immunotherapy ( 33 35 ). As a result, patients with a high level of CDKL3 expression may benefit less from immunotherapy and result in a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study resulted in the identification of 227 mutated genes. Among them, XRCC1 exhibited a substantial number of mutations and was associated with autophagy [ 106 ]. Demirbag-Sarikaya et al observed that the autophagy-related molecule autophagy-related protein 5 (ATG5) interacts with both XRCC5 and XRCC6.…”
Section: Role Of Xrcc In Autophagymentioning
confidence: 99%